Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd004696.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-enriched formula versus standard term formula for preterm infants following hospital discharge

Abstract: Current recommendations to prescribe "post-discharge formula" for preterm infants following hospital discharge are not supported by the available evidence. Some limited evidence exists that feeding preterm infants following hospital discharge with "preterm formula" (which is generally only available for in-hospital use) may increase growth rates up to 18 months corrected age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 52 publications
3
49
0
Order By: Relevance
“…In order to achieve catch-up growth, IUGR neonates are generally fed a formula containing a high density of nutrients [29]. However, high nutritional intake may induce oxidative stress and metabolic syndrome [30], which can be exaggerated in IUGR offspring due to their immature antioxidant defense system [26].…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve catch-up growth, IUGR neonates are generally fed a formula containing a high density of nutrients [29]. However, high nutritional intake may induce oxidative stress and metabolic syndrome [30], which can be exaggerated in IUGR offspring due to their immature antioxidant defense system [26].…”
Section: Discussionmentioning
confidence: 99%
“…Weight and Ht, before 2 years of age measured in horizontal position, were recorded monthly 1 year after full-term age (termed as 1 year of age throughout the text), three-monthly until 2 years and thereafter yearly. HC was measured monthly from full-term age until 1 year of age, at 15 months and at median age of 8.1 years in boys and 9.7 years in girls (range [2][3][4][5][6][7][8][9][10][11][12][13][14]. Infants were considered full term at 40 weeks corrected age.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…Ht and Wt data were available for 72% of the boys and 82% of the girls at term; more than 90% of the children at 1 and 2 years of age and 70% of the boys and 72% of the girls at 10 years of age. HC data were available for 72% of the children at term, 77% of them at 15 months and for 51% at the study visit (mean age of 8 years; range [3][4][5][6][7][8][9][10][11][12][13][14]. Data distribution for Wt after full term was generally positively skewed in girls but normally distributed in boys.…”
Section: Data Qualitymentioning
confidence: 99%
“…Adequate nutrition is important to optimize catch-up growth. A review showed that current recommendations to prescribe nutrient-enriched formula for preterm infants following hospital discharge are not supported by the available evidence [40]. Currently, post-discharge feeding (formula) is given to stimulate growth, but it is still unknown if this stimulates unhealthy catch-up growth.…”
Section: Discussionmentioning
confidence: 99%